DEVELOPING LEARNING MEDIA MONOKARTA TO IMPROVE STUDENT LEARNING OUTCOMES - nandia Gupita (JOSAR (Journal of Students Academic Research), 2021)
Education is a very important means for developing the Indonesian nation to become more developed and developing. Through the world of formal education or the nation's successor genaration can learn and add insight into the science of citizenship. But in the process in the real world these next generation appear to be less interested in learning about state insight. If in learning there is no interest and encouragement from within, what is learned will not be possible to be accepted and understood. This is a challenge for educators to be able to make students interested, enthusiastic, and enthusiastic in participating in learning. One way to overcome this is through learning media that are interesting and in accordance with the times. For this reason, a solution is offered for game-based monokarta learning media. To provide a new atmosphere through the delivery of material. Conceptualizing material more easily so that material is easily delivered and accepted by students. This students are expected to be more interested and motivated in participating in learning so that learning objectives are expected to be achieved maximally.